PRAGMATIC FUNCTIONS OF APHORISMS - Bozorboyeva Xusnida (Journal of new century innovations, 2023)
Abstract: This article provides some information about pragmatic functions in aphorisms, benefits, usage of them. Aphorisms play important role in language. Due to the growing scientific interest in the pragmatic and cognitive aspects of the text against the background of close attention to human speech activity directly related to the processes of meaning formation, including aphorisms.